Smuggling, Currency Substitution and Unofficial Dollarization : A Crime-Theoretic Approach - Mourmouras, Alex.; Russell, Steven (Washington, D.C. : International Monetary Fund, 2000)
Large stocks of U.S. dollars and other hard currencies circulate in the transition economies, in Latin America, and in other countries that have experienced macroeconomic mismanagement. Using a monetary model that combines the legal restrictions and crime-theoretic traditions, this paper demonstrates how leaky exchange controls lead to currency substitution and progressive dollarization. The paper also analyzes the impact of dollarization on the ability of governments to earn seigniorage, the dynamics of dollarization in a growing economy, and the central role of expectations-specifically, confidence in the domestic currency-in determining the extent of dollarization and, potentially, in reversing it.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet